Genetic diversity and introgression analyses in coffee (Coffea arabica L.) using molecular markers - Anthony, F.; Combes, M.C.; Herrera, J.C.; Prakash, N.S.; Bertrand, B.; Lashermes, P. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
5 ilus. 29 ref.